PERAN PERAN WAKAF PRODUKTIF DALAM PEREKONOMIAN: Strategi Pengembangan Wakaf Produktif, Implementasi Peran Wakaf Produktif Dalam Perekonomian - Nurus Shefrilianti Hidayatullah; Maharani, Najwa Zikra; Sunjoto, Arie Rachmat; Aisia, Galih; Rizqon, Abdul Latif (Universitas KH. MUkhtar Syafaat (UIMSYA) Blokagung Banyuwangi, 2025)
A healthy economy is the desire of every country, especially Indonesia. However, the ever-increasing number of poor people is a common global problem. Waqf is an Islamic instrument that can address socio-economic issues. Proper management of productive waqf by a nadzir (manager) can develop the waqf and advance the community's economy. This study aims to identify and analyze the role of productive waqf in economic development. This study uses a qualitative research method with a literature review approach. This research is based on books, journals, articles, information, and other sources relevant to the discussion topic. This study suggests that productive waqf, managed well by a nadzir, can increase waqf productivity. Thus, waqf funds can be used to improve the community's standard of living and create sustainable businesses that can improve the welfare of the community.